Life cycle management of capital construction object with minimization of atmospheric air pollution - V. N. Azarov; O. V. Burlachenko; A. O. Burlachenko; M. D. Azarova (Vestnik MGSU)
Introduction. The existing approaches to management decision-making in construction production give the opportunity to select options only for a certain stage of the capital construction object life cycle (LC CCO), not considering their effectiveness throughout the whole LC. To eliminate this disadvantage, the authors propose a system of information support for the LC CСO management, taking into account the minimization of atmospheric air dust pollution during the implementation of decisions.Materials and methods. Within the framework of a systematic approach to the LC CCO management, the correct criteria choice is of crucial importance, using which an optimal decision can be made. On the other hand, the need to ensure the effectiveness of managerial decisions throughout the LC CCO involves the development of a system that allows to predict the managed object behavior throughout its entire life cycle already in the initial stages. Since the occurrence of various events (situations) during the LC CCO is random, the determination of the probability of occurrence of these or those events is of great importance. Technical means for monitoring atmospheric air pollution by dust particles PM2.5 and PM10 are presented.Results. To take into account other decision-making criteria, besides technical and economic indicators, the experimentally obtained reduced values of dust concentration in atmospheric air are proposed. For this purpose, the sources of such pollution in all the LC CCO stages are systematized. Based on the developed life cycle model, expressions for determining the probability of events occurrence during the LC CCO are obtained. This stochastic model allows you to predict the state of the control object when implementing a particular solution. The application of the proposed methodology made it possible to determine the fine dust concentration and the probability of exceeding the maximum permissible concentration in some types of work to calculate the effectiveness of the considered management decisions.Conclusions. An information support system was built, which, unlike the applied methods, makes it possible to make decisions on the LC CCO management, not only taking into account the technical and economic efficiency of the compared options, but also the degree of atmospheric air dust pollution. In addition, the developed information support allows you to take into account the fact that certain events occurrence is random during the LC CCO with the determination of their occurrence probability.